Analisis Tindak Tutur Ilokusi dalam Teks Anekdot pada Modul Pembelajaran SMA Bahasa Indonesia Kelas X yang Disusun oleh Indri Anatya Permatasari - Safinda Fitriana; Salahuddin Al Ayubi; Lalitta Octavia; Naura Putri; Evi Nur Mala Sari; Zuliyanti Zuliyanti; Asep Purwo Yudi Utomo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The focus of this study is on the illocution of the anecdote text in the learning module of the Class X Indonesian High School Language Learning module compiled by Indri Anatya Permatasari. The existence of this study is used as a basis for explaining the intent of anecdotal texts as well as raising some issues around the community to be understood wisely through understanding the intent of anecdotal texts. In addition, the study also aims to provide an understanding of the classification of illocution speech in anecdotal text in the Indonesian language learning module of class X SMA compiled by Indri Anatya Permatasari. The methods used in this study are two, namely descriptive and qualitative, and use a pragmatic theoretical approach. The data used is in the form of anecdotal text in the X class of the Indonesian language learning module, which is then analyzed according to the classification of illocution speech. The data source in this study is anecdotal text in the learning module. The data collection for this study uses a listening or reading technique and notes. In his data analysis, use agility and body techniques. As for data presentation, it uses formal and informal techniques. The results of the data analysis found the action of assertive, directive, expressive, declarative, and commissive illocumentation. The most-finding data is assertive illocution speech, while the least is commissionive illocution speech. Hopefully, this article can provide an understanding of the classification of illocution speech in anecdotal text in a learning module.